IMPROVING ACCESS TO HIGHER EDUCATION FOR LOW-INCOME HIGH SCHOOL STUDENTS THROUGH PIP AND STUDENT’S MENTORSHIP: SCHOLARSHIP AWARDEE EXPERIENCES IN LOMBOK - Mashur, Mashur (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The low-income high school students culturally have had very challenging experiences to go to colleges or universities. As experienced by the participants, they tend to have more difficulties compared to the high-income school students.  PIP (Program Indonesia Pintar) is financial aid in the form of cash, expanded access, and learning opportunities from the Indonesian government for students who come from low-income and vulnerable families to finance their education, to increase the number of education sustainability and to decrease the dropout rate from the primary school level to senior high school level in Indonesia. There are 31 students involved in this study which are 15 males and 16 females. These samples of the study were the recipients of the KIP-Kuliah, GenBi and campus scholarship from three universities in Indonesia. In collecting the information, the novice researcher did literature review and disseminated an online survey with open-ended questions to the scholarship recipients regarding their experiences before getting into and during study in the universities to provide evidence on the uses of PIP and the benefits of student’s mentorship. Besides, the researcher exploited sharp discontinuities in the program eligibility formula to identify and analyze the impact of the PIP and student mentorship for the low-income student outcomes at different level of study at the level of freshmen, sophomore, junior and senior at their universities.